Optimalisasi Penjualan Gula Kristal Putih melalui Lelang di PT Sinergi Gula Nusantara - Aniyah, Dhiyaul; Aminah, Siti (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2025)
The optimization of white crystal sugar (GKP) sales management through auctions is an effort undertaken by PT Sinergi Gula Nusantara to enhance efficiency in product distribution and marketing. This study aims to analyze the auction mechanism as a strategy to determine fair pricing, improve operational efficiency, and strengthen the company’s market position. The research method used is descriptive with a qualitative approach, which includes the analysis of sugar distribution channels and the stages of the auction process. The results indicate that auctions provide price transparency beneficial to all parties, increase distribution efficiency, and help reduce price uncertainty commonly encountered in sugar sales. The auction process, involving several stages such as sales submission and buyer approval, demonstrates its effectiveness in optimizing sale prices and distribution. In conclusion, the implementation of the auction system in the sale of GKP by PT Sinergi Gula Nusantara has proven to enhance efficiency and market trust, as well as assist in managing larger sales volumes with prices aligned with market conditions.